Effect of SGLT2 inhibitor (Empagliflozin) on HbA1c in most Prevalent Age Group of Type 2 Diabetic Patients - ., Nizamuddin (International Journal of Pathology, 2023)
Background: The new anti-diabetic drugs, which are known as sodium-glucose transport 2 (SGLT-2) inhibitors, remove about 80 to 100 grams of glucose per day from the bodyObjective: Our objective is to evaluate the effect of SGLT2 inhibitor (Empagliflozin) on HbA1C in T2DM patients.Method: The study was conducted in department of Medicine, Khyber teaching hospital Peshawar from October 2020 to September 2021. Total 400 newly diagnosed diabetic patients in accordance with American diabetes association (ADA) guidelines, with age group 45 to 55 years were enrolled in the study. All the patients were counsel verbally and after willingness, proper consent was singed from each patient. All the demographics were recorded on purposefully design proforma and SGLT2 inhibitors empagliflozin 10mg once daily was prescribed to the patients. All the patients were followed for 6 months with two follow-up intervals at 3 and 6 months.Results: In total 400 patients, 123 (30.8%) were female and 277(69.3%) were male. The mean age was 50.13 ± 3.3 years. The mean starting HbA1C was 9.12 ± 0.46% while the mean HbA1C at subsequent follow-ups was 8.7 ± 0.46 and 8.4 ± 0.4% respectively. Gender does not affect the study variables significantly with p-value >0.05. Statistical strong significant differences were observed in HbA1C values at time of enrollment of patients (9.12 ± 0.46%) and after follow-up1 (8.7 ± 0.46) and follow-up 2 (8.4 ± 0.4%) with p-value <0.001.Conclusion: Empagliflozin was found to improve diabetic profile of the patients. Our results need replication with a larger data from multiple centers to further validate our findings.